THE EFFECT OF COUNTRY OF ORIGIN (COO) AND BRAND IMAGE ON CONSUMER SATISFACTION MEDIATED BY PURCHASE DECISION IN WULING CARS IN PALU CITY - Riky Thias Pranolo Tobondo; Syamsul Bachri; Maskuri Sutomo; Mohammad Zeylo Auriza (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of Country of Origin (COO) and brand image on consumer satisfaction, with purchase decision as a mediating variable among Wuling car consumers in Palu City. The research employed a quantitative approach with data collected through questionnaires distributed to 106 respondents who are users or consumers of Wuling cars. Data analysis was carried out using SmartPLS 4 software. The findings indicate that Country of Origin has a significant effect on both purchase decisions and consumer satisfaction, directly and indirectly. Brand image also has a significant effect on purchase decisions and consumer satisfaction, as well as an indirect effect through purchase decisions. Furthermore, purchase decision acts as a significant mediating variable in the relationship between Country of Origin and brand image on consumer satisfaction. The results imply that Wuling’s corporate strategy should focus on strengthening COO reputation and brand image through innovation, quality, and effective marketing communication strategies.